The rule of law and the economy: Bankers, brigands and bounders. (June 2016) - Green, Nicholas
The vigour of the legal system is critical to the success of the economy; and the integrity of the rule of law is critical to the legal system. The common law has, over many centuries, demonstrated its potency as a driver of international trade to the United Kingdom. In a troubled time (politically and economically) the need for a strong legal system committed to the rule of law is never more critical. Yet there are present threats to the legal system and the rule of law and political intervention risks creating unexpected and harmful consequences which will hinder the economy.